CagA and VacA Gene Expression in Helicobacter pylori Infected Patients in Dr. Soetomo General Hospital - Burhana Mawarasti; Herry Purbayu; Lindawati Alimsardjono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2016)
Marshall and Warren had discovered helicobacter pylori in 1982 and known as the main pathogen caused infection on human’s stomach. Helicobacter pylori is a bacillus spiral and gram negative bacteria which is motile as it has almost six flagella on one side of its body (unipolar). There are strain type I, intermediate and type II. Strain type I has cytotoxin associated gene A (cagA) and vacuolating cytotoxin gene A (vacA) while strain type II has vacuolating cytotoxin gene A (vacA). Because of cag pathogenicity island (PAI), strain type I has the tendency to cause the infection become more malignant. This study was conducted by using descriptive purposeful sampling method on patients in endoscopy department of internal medicine in the division of hepatology gastroentero Dr. Soetomo starting from October 20 until November 25, 2015. The aim of this study is to determine whether the stool sample shows cagA gene and or vacA gene. The data was proceed by observation through the results of PCR assays to look at the genes that are expressed by Helicobacter pylori. DNA was extracted from stool by using QIAamp (Qiagen) stool kit. Results of the study show only one patient positive for vacA gene while cagA gene is none from ten patients. DNA examinations with different concentrations and temperatures also show the same results. One sample from the stool specimen shows positive for strain type II, indicates it only has vacA gene. PCR examination through gastric biopsy is known has higher specificity.